They were men sent form God a centenary record (1836-1936) of gospel work in India among Telugus in the Godavari Delta and neighbouring parts - Bromley, E.B. (Bangalore, India The Scripture Literature Press, 1937)
Includes photos and maps.
Brethren writer.
Keywords: Brethren movement -- Missions -- India